Short-Term Outcomes and Clinical Features Analysis of Anterior Cervical Discectomy; Effect of Non-Instrumented Vs. Instrumented Fusion - Faryal, Madiha Ahsan, Afnan, Waleed Ali, Sajid Khan, Zohaib Ali, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To investigate the impact of instrumental and non-instrumental anterior cervical decompression and fusion procedures on various cervical degenerative diseases in terms of reducing pain and disability. Study Design: A prospective case series. Place and Duration: The study was conducted in the Neurosurgery Ward of Ayub Medical Complex, Abbottabad and Neurosurgery department of Hayatabad Medical Complex, Peshawar for duration 1 year from 1st Jan 2021 to 31st Dec 2021. Material and Methods: A total of 40 patients who underwent surgery for cervical degenerative diseases were selected and patients with more than one level segment were excluded from the study. Clinical symptoms and preoperative pain and disability were recorded using the Japanese Orthopaedic Association (JOA) score, visual analogue scale (VAS) and the Nurick grading. Post-operative score was recorded with improvement or deterioration in VAS, JOA score, and Odom criteria. Results: 40 patients, 24 (60%) men and 16 (40%) women were enrolled in the analysis. The mean age was 56.6 years ± 6.7 SD. Mean length of symptoms was 12.05 months with 5.65 SD. The total mean span of stay in the postoperative period was 4.55 days ± 1.05 SD. 24 (62.5%) patients reported neck pain, 18 (45%) patients with symptoms of radiculopathy, and 12 (30%) sensory deficits. In the study, 13 (32.5%) patients had features of cervical myelopathy. There was hand weakness in 11 (27.5%) cases and reduced range of neck motion in 15 (37.5%) cases. Anterior cervical decompression and fusion (ACDF) were performed in 24 (60%) patients, and anterior cervical discectomy (ACD) was performed in only 16 (40%) patients. The median of pre-operative VAS was 7.9 (mean 7.2) ± 1.35 SD, and the median of post-operative VAS after 2 weeks of follow-up was 3.00 (mean 3.04) ± 0.64 SD and 2.00 (mean 1.91) ± 0.94 SD after 3-month follow-up. Similarly, the median pre-operative JOA score was 15.20 (mean: 12.7) ± 3.30 SD, and after 3 months of follow-up, it was 16.00 (mean: 15.5) ± 1.01 SD. The reduction of the median VAS (Z = -4.46) and JOA (Z = -4.22) scores for both intervention groups was statistically significant after 3 months of follow-up (p <0.001). Conclusions: Anterior cervical procedures are associated with excellent short-term outcomes in reducing pain and disability. ACDF requires longer operative time, but the length of postoperative stay was comparable in both groups.